L’expulsion du métropolite copte Yā‘ǝqob (1337-1344) par le roi ‘Amda Ṣǝyon (1314-1344) : une politique de tolérance vis-à-vis des communautés musulmanes d’Éthiopie ? - Martina Ambu (Revue des Mondes Musulmans et de la Méditerranée)
This contribution aims to expand the extant investigations on the confrontations that took place between the Christian king of Ethiopia ‘Amda Ṣǝyon (1314-1344), the Egyptian metropolitan Yā‘ǝqob (1337-1344) and the missionary monks from the Takla Haymānot’s network. In order to do so, it will study an extensive hagiographic dossier, dating between the 14th and the 16th centuries, which contains many valuable elements that explain the policy adopted by ‘Amda Ṣǝyon towards his Muslim subjects. Through the analysis of the hagiographic sources within the framework of the period in which they were written, this study attempts to identify the reasons why the Ethiopian king sent the supreme leader of the Ethiopian Church Yā‘ǝqob back to Egypt in 1344.